Keragaman Jenis dan Aktivitas Mengisap DarahAnopheles spp. di Desa Simpang EmpatKecamatan LengkitiOgan Komering Ulu Sumatera Selatan - Vivin Mahdalena; Nungki Hapsari; Tanwirotun Ni’mah (ASPIRATOR - Journal of Vector-borne Disease Studies, 2016)
Lengkiti districts have high number of malaria cases with Annual Paracite Incidence (API) was 13.02 ‰in 2012. The entomology information aboutthe vector mosquito species is needed in vector control purpose. However, information about Anopheles spp. in Simpang Empat Village of District Lengkiti is unknown. The purpose of this study was to identify the diversity of Anopheles spp., which potentially acts as vectors of malaria. Research was conducted in Simpang Empat village, Lengkiti district, Ogan Komering Ulu (OKU), South Sumatra, from March to October 2014 which. This research collected adult mosquitoes; both by human and cattle bait traps methods. The results showed that there were 10 species of Anopheles spp. caught along 8 catching times with Anopheles philippinensis as the most captured species. Biting activity of Anopheles spp. was higher outside of the houses and it occured all night except at 01.00-02.00 a.m and at 04.00-05.00 a.m, a biting peak was at 06.00-07.00 p.m. Man Hour Density (MHD) inside and outside of houses ranged from 0.0025 to 0.0075 mosquito/ person/ hour. Anopheles spp. that have been found were An. philippinensis, An. vagus, An. maculatus, An. minimus, An. kochi, An. barbirostris, An. flavirostris, An. leucosphyrus group, An. sinensis and An. nigerrimus. An. vagus density was highest in outdoors, , while An. philippinensis was the most dominant mosquito.